How Selling Online Is Affecting Informal Firms in South Asia - MAURIZIO BUSSOLO; AKSHAY DIXIT; ANNE GOLLA; ANANYA KOTIA; JEAN N. LEE; PREMA NARASIMHAN; SIDDHARTH SHARMA (Asian Development Review)
Understanding how e-commerce platforms are affecting the small, informal firms that sell on them is a question of growing importance to researchers and policymakers in developing countries. This paper examines this question using data from surveys of firms selling on two e-commerce platforms in South Asia. The businesses selling on these platforms range widely in terms of size, degree of formalization, and other characteristics. Their main reason for joining the platforms is to access more customers. After joining, many sellers report (i) an expansion of their business, (ii) an increase in their incentive to formal registration, and (iii) increased visibility to tax authorities. Other less-widespread channels of impact include (i) the adoption of new or improved business practices and technologies, (ii) better access to finance, and (iii) greater flexibility in balancing home and work life. These reported impacts do not vary significantly by firm size or registration status, suggesting that the greater market access brought about by (selectively) joining e-commerce platforms benefits equally large and small (informal) firms. Given size and age, firms selling on the platform for a longer period are more likely to experience these impacts, suggesting that firms learn how to use the platform more effectively over time. Finally, firms on these platforms—even the micro and small ones, which tend to be informal—are from a select group, as they are owned and managed by individuals who are more educated and younger than the owners and managers of more typical firms in this setting.